The determination of the relation between some parameters of Turkey man volleyball 1. and 2. league players - Ozgur, T.; Ozgur, B.; Kolayis, H. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of this study was to investigate the determ?nat?on of the relat?on between some parameters of turkey man volleyball 1. and 2. league l?bero players. Material & Methods The data were collected from 16 libero players whose ages were approximately 24,06 2,9 from 1. and 2. league. In this study, takei digital vertical jump meter, prosport TMRESC 2200 multigate telemetry chronograph (for 5-10 meter sprint time), newtest 1000 (reaction time), takei Grip-D strength dinamometer, takei back strength dinamometer, takei flexion-D standing trunk flexionmeter were used for collecting the data. The collected data were analysed by descriptive statistic technics and Pearson correlation technics. Significance was set at the p<0,05 level. Data was analysed by SPSS for Windows. Results The results showed that there were significant correlation among following parameters; leg strength and vertical jump (r: 0,450, p<0,05), leg strength and left hand grip strength (r:0,466, p<0,05), leg strength and rigth hand grip strength (r:0,720, p<0,05), leg strength and rigth hand auditory reaction time (r:-0,499, p<0,05), vertical jump and rigth hand auditory reaction time(r:-0,492, p<0,05), vertical jump and left hand grip strength (r:0,458, p<0,05), broad jump and rigth hand visual reactin time (r:-0,507, p<0,05), broad jump and vertical jump (r:0,787, p<0,05), broad jump and rigth hand auditory reaction time (r: -0,708, p<0,05), broad jump and rigth hand grip strength (r: 0,455,p<0,05), broad jump and left hand grip strength (r:0,504, p<0,05), rigth hand visual reactin time and left hand visual reactin time(r: 0,849, p<0,05), rigth hand visual reactin time and rigth hand auditory reaction time (r:0623, p<0,05), rigth hand grip strength and left hand grip strength (r:0,758, p<0,05). Conclusions Trainers should select and train players whose have long extremities and also agile, fast, speed and good at auditory and visual reaction time. Besides, training programs should designed to improve these abilities.